(untitled) (International journal of artificial intelligence, 2026)
This article examines contemporary technologies and methodological approaches for developing social motivation in preschool-aged children. Social motivation, defined as the intrinsic drive to engage with others, understand social cues, and participate in collective activities, serves as a fundamental component of child development and school readiness. The research analyzes the theoretical foundations of social motivation formation, explores age-specific characteristics of preschoolers that influence motivational development, and presents evidence-based pedagogical technologies for fostering prosocial behaviors, cooperative skills, and interpersonal competencies. Through systematic analysis of both traditional and innovative approaches including play-based learning, project methods, storytelling techniques, digital technologies, and socio-dramatic activities, this study demonstrates that intentional implementation of structured motivational technologies significantly enhances children's social-emotional development, peer relationships, and readiness for formal education. The article provides practical recommendations for educators, psychologists, and parents working with preschool children in various educational settings.